Pregnancy Relationship Through The Months The Event Of The Neonatorum Asfixia In Bulukumba District - Andi Nurlaily; Irmawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
Post date pregnancy is one of the pregnancies that are at risk, this case can cause many risks and the higher complication either for mothers or the baby who had beenborn couldhave asphyxia. The purpose of the study is to find out the relationship of post date pregnancy and the incident of asphyxia neonatorum. The type of the study used was analytic survey with historical cohort research design. The population sample was all maternity mothers in RSUD H. A. Sulthan Daeng Radja Bulukumba 2016 was 1526. The sample was 307 people. The sampling technique used is probability sampling with systematic random sampling. The instrument taking used was performed through observation. Data were analyzed by Chi-Square with Î± 0.05 and Relative Risk test (RR). The result of this study found that the analyzed by Chi Square test obtained (p-value: 0,00) and relative risk value 3.066. which means that there was relationship of post date pregnancy and the incident of asphyxia neonatorum in RSUD H. A. Sulthan Daeng Radja Bulukumba 2016, with a relative risk value (RR) of 3.066 means that mothers who have a post date at risk 3 times more childbearing asphyxia compared with pregnant aterm. It is recommented for midwifes to be more cautions in determining the age of the pregnancy so that the incident of the asphyxia neonatorum can be minimized.